Maternal perception, concern and dissatisfaction with child weight and their association with feeding practices in the Generation XXI birth cohort. Issue 7 (14th April 2022) - Costa, Alexandra; Hetherington, Marion M.; Oliveira, Andreia
Abstract: What a mother thinks about her child's weight status might influence what and how she feeds her child. We examined the association between maternal perception, concern and dissatisfaction with child weight alongside feeding practices. Participants were from the Generation XXI birth cohort ( n = 3233). A validated version of the Child Feeding Questionnaire and the Overt/Covert Control scale were used. Associations were evaluated by linear regression models ( β coefficients and 95 % confidence intervals (95 % CI) with Bonferroni correction). Perceived underweight was associated with practices promoting food intake, such as higher pressure to eat at ages 4 and 7 years ( β = 0·229; 95 % CI: 0·059, 0·398 and β = 0·190; 95 % CI:0·005, 0·376, respectively) and lower restriction at age 4 ( β = –0·175; 95 % CI: –0·0310, –0·039). At age 7, perceived overweight was associated with higher covert control ( β = 0·203; 95 % CI: 0·029, 0·376). Mothers who were concerned about child weight reported higher restriction ( β = 0·226; 95 % CI: 0·142, 0·310 at 4 years and β = 0·261; 95 % CI: 0·169, 0·353 at 7 years) and covert control ( β = 0·183; 95 % CI: 0·083, 0·282 at 4 years and β = 0·171; 95 % CI: 0·073, 0·269 at 7 years). Maternal desire for a heavier child was associated with higher pressure to eat at both ages ( β = 0·285; 95 % CI: 0·163, 0·406 and β = 0·393; 95 % CI: 0·266, 0·520), while the desire for a thinner child was related to higher covert control at 7 years of age ( β = 0·158; 95 % CI: 0·001, 0·316). Maternal perceptions and concern for child weight status are associated with feeding practices independently of actual weight status.